Flagship 5: Governance of natural resources - CGIAR Research Program on Policies, Institutions, and Markets (International Food Policy Research Institute, 2018)
Strengthening tenure over land, water, trees, and other natural resources for the poor, particularly women ● Facilitating shared use of resources within landscapes ● Governance of natural resources for sustainability and harmony